PROSPEK PENJUALAN RUMAH PADA PERUMAHAN CITRALAND SAMARINDA - -, Henry Lesnussa (EKONOMIA, 2015)
The purpose of this study to find out the prospect of house sales at The Citraland City Samarinda Regency on years of 2015 and 2016 that predicted will be increase.Formulation of the problem in this study is â€œDoes the Sale of House in the Citraland City Samarinda Regency will be increase on 2015 and 2016 in Samarinda City?â€ Hypothesis in this study is: Prospect of the house sales in the Citraland City Regency in 2015 till 2016 will be increase.Analytical Method and hypothesis used the Least Squares Method, consist of: Sales Forecasting Future, includes times function (Yt), intersection or point of contact between vertical line at the time t = 0 (), Slope Line (), Time (t) which in this study is indicated in semester, and total of data (n).The theory used in this study is the marketing management theory that focuses on sales, includes the meaning of marketing, meaning of marketing management, marketing functions, marketing concept, the different between marketing concept and sales concept, market segmentation, target markets, marketing mix, distribution strategy, sales forecast, and types of forecasting.The data used is secondary data, and method of collecting data in this study is Field Work Research, that is study was made on site andÂ in the office of PT. Ciputra Graha Mitra Samarinda in order to obtain of data required and library research, thatÂ is to collect data from literature was related to this study.Results of analysis show that Prospect of House Sales at The Citraland City Samarinda will be increase in years of 2015 and 2016, therefore the hypothesis of this study is be accepted.